2019
DOI: 10.1177/0954405419883055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of material removal state on the selection of theoretical models when scratching single-crystal copper using the load modulation approach

Abstract: This article presents a constant force–controlled cutting approach with two different geometries of cutting tools. The methodologies for establishing two theoretical models were proposed to quantitatively predict the required applied normal forces at the expected machined depths, which were obtained with a solution to the horizontal projection of the sample–tip contact area and the multi-edge form tip based on a generalized cutting approach, respectively. The selection of the proposed theoretical models is dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Figure 1 shows the schematic representation of machining periodic microstructures on the flat and curved surface by MTD tool under constant or variable forces. The experimental configuration and the cutting principle of proposed tip-based force control system are illustrated in the previous study [28]. This modified four-axis micromachining system consists of two high-precision stages (X,Y) driven by air floatation with the resolution of 1 nm, a motor driven coarse stage (Z) with the resolution of 0.5 μm and an air-bearing rotary stage (C) with radial rotation accuracy 0.26 μm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Figure 1 shows the schematic representation of machining periodic microstructures on the flat and curved surface by MTD tool under constant or variable forces. The experimental configuration and the cutting principle of proposed tip-based force control system are illustrated in the previous study [28]. This modified four-axis micromachining system consists of two high-precision stages (X,Y) driven by air floatation with the resolution of 1 nm, a motor driven coarse stage (Z) with the resolution of 0.5 μm and an air-bearing rotary stage (C) with radial rotation accuracy 0.26 μm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The results indicate that when the wire-line velocity is constant, with the increase of the feeding force the maximum cutting depth increases. Yan et al 17 presented a constant force–controlled cutting approach with two different geometries of cutting tools. Two theoretical models were proposed to quantitatively predict the required applied normal forces at the expected machined depths, which were obtained with a solution to the horizontal projection of the sample–tip contact area and the multi-edge form tip based on a generalized cutting approach, respectively Li et al 18 conducted experiments and found that certain feed angles of the diamond wire saw can be chosen to obtain the least surface shape deviation and reduce the influence of anisotropy of silicon.…”
Section: Introductionmentioning
confidence: 99%
“…Scratching tests are mostly used to investigate the material damage removal mechanism, [32][33][34][35][36] and unidirectional C f /SiC composites can effectively avoid the interaction of fibers in different directions, which is an ideal method to understand the removal mechanism. Li et al 37 conducted single grit grinding mechanism of C f / SiC through finite element simulation by analyzing the grinding forces and related fracture features.…”
Section: Introductionmentioning
confidence: 99%